2012
DOI: 10.5501/wjv.v1.i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Emerging and re-emerging viruses: A global challenge illustrated by Chikungunya virus outbreaks

Abstract: In recent decades, the issue of emerging and reemerging infectious diseases, especially those related to viruses, has become an increasingly important area of concern in public health. It is of significance to anticipate future epidemics by accumulating knowledge through appropriate research and by monitoring their emergence using indicators from different sources. The objective is to alert and respond effectively in order to reduce the adverse impact on the general populations. Most of the emerging pathogens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 53 publications
0
22
0
3
Order By: Relevance
“…31,32 None of the CHIKV strains analyzed in this study had a valine subsititution at position 226 in the E1 protein, which has been associated with major recent epidemics in Asia and the Indian Ocean. 33 This finding suggests genetic stability and low rates of molecular evolution of the enzootic strains circulating in West Africa. However, the presence of WAF II in the ECSA lineage suggests the epidemic potential of this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 None of the CHIKV strains analyzed in this study had a valine subsititution at position 226 in the E1 protein, which has been associated with major recent epidemics in Asia and the Indian Ocean. 33 This finding suggests genetic stability and low rates of molecular evolution of the enzootic strains circulating in West Africa. However, the presence of WAF II in the ECSA lineage suggests the epidemic potential of this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported CHIKV circulation in West Africa, especially in Nigeria between 1963 and 1977 [ 6 , 7 ]. Major CHIKV epidemics were recently reported in Africa and Asia [ 8 ]. A significant outbreak occurred in Italy in 2007, and numerous imported cases have been detected elsewhere in Europe and the United States of America [ 9–13 ], emphasizing CHIKV as a re-emerging public health threat worldwide.…”
mentioning
confidence: 99%
“…Vaccination is the most effective way to prevent viral infectious diseases, which saves millions of lives every year, yet the current long and laborious journey to develop antiviral vaccines is very inefficient 5 . More challengingly, virus evolves rapidly to escape the old vaccine-induced immunity by changing its genome architect 6 . Therefore, new biotechnologies to facilitate and accelerate vaccine development against novel emerging and re-emerging viruses are desperately needed, for the endless arms race with the dynamically evolving virus.…”
mentioning
confidence: 99%